ANALISIS PERMINTAAN MAAF BAHASA JEPANG RAGAM BAHASA INFORMAL DALAM ANIME “KUROKO NO BASUKE” - Adhitya Andiny; Hana Nimashita; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to know the types and influences of language variation of japanese apologize in informal language based on language variation factors. They are sosiolect, idiolect and situational factor. Data is taken from Japanese animation titled “Kuroko no Basuke” by Tadatoshi Fujimaki episode 2, 3, 5, 8, 9, 12, 14, 15, 16 and 23. Data collection‟s method is “simak” method and using a “simak bebas libat cakap” technic and taking note method. Data analyse‟s method is identity method and using a dividing-key-factors technique. Based on this research, founded 11 types of japanese apologize in informal language. They are sumimasen, suimasen, sumimasen deshita, sumanai, suman, suman na, suman no, gomen, gomen ne, warui and warukatta. The using those types is influenced by three sosiolect aspect. They are age, sex and profession. Idiolect and situasional factor also have an influence of using the japanese apologize in informal language.Keywords: apologize, language variation, sosiolect, idiolect